2015
DOI: 10.7182/pit2015153
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of Low-Dose Sulfamethoxazole/Trimethoprim for Pneumocystis Jirovecii Pneumonia Prophylaxis in Kidney Transplant Recipients

Abstract: Background- Pneumocystis jirovecii pneumonia (PCP) is an opportunistic infection seen in immunosuppressed patients, including solid-organ transplant recipients. Sulfamethoxazole/trimethoprim (SMX/TMP) has long been considered first-line therapy for PCP prophylaxis. Optimal dosing regimens in solid-organ transplant recipients have not been fully defined. Objective-To examine the tolerability of a 1-year, 3-times weekly, prophylactic regimen of a single-strength SMX/TMP tablet. Study Design-Single-center, retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…However, this suggestion is noted to be based on evidence of moderate quality 32 . Reported rates of TMP‐SMX intolerance in renal transplant recipients due to drug‐related adverse effects range from 2.6% to 38% 18,19,22,33 . These patients require PCP prophylaxis with alternate agents such as atovaquone, dapsone, or aerosolized pentamidine which lack coverage against other common infections including UTI.…”
Section: Discussionmentioning
confidence: 99%
“…However, this suggestion is noted to be based on evidence of moderate quality 32 . Reported rates of TMP‐SMX intolerance in renal transplant recipients due to drug‐related adverse effects range from 2.6% to 38% 18,19,22,33 . These patients require PCP prophylaxis with alternate agents such as atovaquone, dapsone, or aerosolized pentamidine which lack coverage against other common infections including UTI.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of TMP‐SMX for reasons of myelosuppression also appears unfounded, as rates of leukopenia in solid organ transplant cohorts when TMP‐SMX is employed as prophylaxis have been reported at less than 2% . Modern studies have suggested that TMP‐SMX therapy when employed as prophylaxis in hematological malignancy does not impact on the degree or duration of neutropenia .…”
Section: Discussionmentioning
confidence: 99%
“…13 We observed suboptimal G6PD screening in our dapsone patient cohort, with less than half under- The avoidance of TMP-SMX for reasons of myelosuppression also appears unfounded, as rates of leukopenia in solid organ transplant cohorts when TMP-SMX is employed as prophylaxis have been reported at less than 2%. 16,17 Modern studies have suggested that TMP-SMX therapy when employed as prophylaxis in hematological malignancy does not impact on the degree or duration of neutropenia. 18 A recent Cochrane review of PJP prophylaxis in the non-HIV setting found no difference in adverse events requiring discontinuation when comparing TMP-SMX to no treatment or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Medications used post-transplant are thought to be the major cause for post-transplant hyperkalemia in recipients with a well-functioning graft. Use of trimethoprim in Trimethoprim/Sulfamethoxazole (TMP/SMX) in standard doses contributes to hyperkalemia by ENaC blockade ( 7 ) but the incidence is low especially when the regimen comprises of single strength tablet three times weekly for Pneumocystis and urinary tract infection prophylaxis ( 8 ). Use of pentamidine can also cause hyperkalemia by a similar mechanism ( 9 ).…”
Section: Hyperkalemiamentioning
confidence: 99%